Study of TH 1 and TH 2 activity in women with threatened miscarriages - Jain, Madhu; Hassan, Zahida; Jain, Shuchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Successful pregnancy is associated with T helper-type 2 (Th2) immunity and is helpful in maintaining pregnancy, while T helper type-1 (Th1) activity is responsible for deleterious effects. Methods: The study comprised of two groups: Group I- Threatened abortions in first trimester (n=60) subdivided in two groups: 1 N- one who continued pregnancy (n=38), and another, 1A- who aborted (n=22), and Group II- 40 pregnant women in first trimester who later delivered at term without any history of abortion in the past. Blood was collected and analyzed for IL-2 and IL-6 by ELISA kit. Results: Th1 activity (IL-2) was higher in threatened abortion group irrespective of whether continuing their pregnancy or aborting in comparison to control (p <0.001). On the other hand, Th2 activity (IL6) was decreased (p <0.001) in both the groups of threatened abortions. Conclusions: The patients with threatened abortion have a definite increase in Th1 activity and decrease in Th2 activity whether aborting or continuing their pregnancy in comparison to normal pregnant women without any history of spontaneous abortion in the past.